Developing lacustrine sedimentary records of storminess in southwestern New Zealand. (1st February 2022) - Fitzsimons, Sean; Howarth, Jamie
Abstract: Variability of the Southern Hemisphere westerly winds (SWW) are the dominant feature of the climatology of the Southern Hemisphere and they are reflected in the Southern Annular Mode (SAM) which is defined as the difference in the zonal mean sea level pressure at 40°S and 65°S and is expressed as a latitudinal movement in the westerly circulation system. Meteorological data suggests that the SAM plays an important role in modern weather and climate of the Southern Hemisphere. Palaeostudies show that the westerly circulation system established its northern limits of present day airflow by the mid Holocene but the records from South America remain out of phase with those from the SW Pacific. In this study we report on the development of a flood frequency hydrological proxy that is based on the recognition of rapidly deposited layers preserved in lake sediments in southern South Island, New Zealand. Four distinct climate states can be identified: low storm frequency between 10 and 8 cal ka BP; moderate storm frequency between 8 and 5.5 cal ka BP, high storm frequency between 5.5 and 4 cal ka BP and low storm frequency between 4 cal ka BP and 750 cal a BP. A post-750 cal a BP increase storm frequency is likely to be a result of Polynesian vegetation disturbance. These four distinct climate states are driven by variations in the strength or persistence of westerly airflow. Comparison with similar records from east coast of the North Island, New Zealand and Ecuador suggest that all three sites experienced an increase in storm frequency in the middle Holocene. Divergence in the records in the late Holocene can be attributed to variability in the strength of ENSO and SAM in different locations. Highlights: Development of a Holocene storm frequency record for the southern South Island, New Zealand. Reconstruction based on lake sediments and chronology from 28 AMS 14 C dates from leaf macrofossils. Four distinct climate states are identified including a period high storm frequency between 5.5 and 4 ka BP. The four distinct climate states are driven by variations in the strength or persistence of westerly airflow.